2017
DOI: 10.1016/j.energy.2017.05.165
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ultra low temperature district heating systems with utility plant and booster heat pumps

Abstract: Document Version Peer reviewed versionLink back to DTU Orbit Citation (APA): Ommen, T. S., Thorsen, J. E., Markussen, W. B., & Elmegaard, B. (2017). Performance of ultra low temperature district heating systems with utility plant and booster heat pumps. Energy, 137, 544-555.Please cite this article as: Ommen T, Thorsen JE, Markussen WB, Elmegaard B, Performance of ultra low temperature district heating systems with utility plant and booster heat pumps, Energy (2017), AbstractThe optimal integration of booster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…Although they found the mixed working fluids resulting in a higher investment cost, the economic performance was comparable to the pure fluids while the mixtures showed similar performance as the pure fluids at off-design conditions. Ommen et al [18] analyzed the performance of ULTDH systems with utility plant and booster heat pumps, observing a performance improvement of 12% for the reference calculations when the system was supplied by central heat pumps. In another work, they designed a new heat pump furnished substation configuration for multifamily buildings in ULTDH systems, finding it energetically and economically interesting [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although they found the mixed working fluids resulting in a higher investment cost, the economic performance was comparable to the pure fluids while the mixtures showed similar performance as the pure fluids at off-design conditions. Ommen et al [18] analyzed the performance of ULTDH systems with utility plant and booster heat pumps, observing a performance improvement of 12% for the reference calculations when the system was supplied by central heat pumps. In another work, they designed a new heat pump furnished substation configuration for multifamily buildings in ULTDH systems, finding it energetically and economically interesting [19].…”
Section: Introductionmentioning
confidence: 99%
“…Elmegaard et al [19]compare the performances of different system configurations with supply temperature at 45 °C, and find the R134a HP system with hot water tank on the primary side reach the highest exergy efficiency. Ommen et al [20] conduct theoretical investigation on the optimal use of booster HP in ULTDH for new buildings, and find the booster HPs can improve the system performance if the central HP is used for heat supply. Torio et al [21] concluded that the geothermal heat pump is a low exergy energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…Yang found that a decentralized substation system with an instantaneous heat exchanger was the best exergo-economic solution in the case that the district heating temperature is high enough for SHW heating. Ommen et al [15] investigated the optimal integration of a heat-pump booster in an ultra-low-temperature district heating system. Analyzing two possible heat sources, i.e., combined heat and power (CHP) and a central heat pump, the study was made for an energy-efficient, multi-family residential building where heating and SHW accounted for equal shares of the demand.…”
Section: Introductionmentioning
confidence: 99%